Exploiting the interactions between the ruthenium Hoveyda–Grubbs catalyst and Al-modified mesoporous silica: the case of SBA15 vs. KCC-1. Issue 14 (13th March 2018) - Werghi, Baraa; Pump, Eva; Tretiakov, Mykyta; Abou-Hamad, Edy; Gurinov, Andrei; Doggali, Pradeep; Anjum, Dalaver H.; Cavallo, Luigi; Bendjeriou-Sedjerari, Anissa; Basset, Jean-Marie
Abstract : 2 nd generation Hoveyda–Grubbs catalyst immobilized onto well-ordered 2D hexagonal (SBA15) and 3D fibrous (KCC-1) mesostructured silica displaying tetra-coordinated Al–H via Surface Organometallic Chemistry (SOMC). Abstract : Immobilization of the 2 nd generation Hoveyda–Grubbs catalystHG-II onto well-ordered 2D hexagonal (SBA15) and 3D fibrous (KCC-1) mesostructured silica, which contained tetra-coordinated Al, has been investigated through the Surface Organometallic Chemistry (SOMC) methodology. The main interest of this study lies in the peculiarity of the silica supports, which display a well-defined tetrahedral aluminum hydride site displaying a strong Lewis acid character, [(Si–O–Si)(Si–O–)2 Al–H]. The resulting supported Hoveyda–Grubbs catalysts have been fully characterized by advanced solid state characterization techniques (FT-IR, 1 H and 13 C solid state NMR, DNP-SENS, EF-TEM…). Together with DFT calculations, the immobilization ofHG-II does not occur through the formation of a covalent bond between the complex and the Al-modified mesoporous silica as expected, but through an Al⋯Cl–[Ru]-coordination. It is not surprising that in functionalized olefin metathesis of diethyldiallyl malonate, DEDAM (liquid phase), leaching of the catalyst is observed which is not the case in non-functionalized olefin metathesis of propene (gas phase). Besides, the results obtained in propene metathesis withHG-II immobilized either on SBA15 ( d pore = 6 nm) or KCC-1 ( d pore = 4 or 8 nm) highlight the importance of the accessibility of the catalytic site. Therefore, we demonstrate that KCC-1 is a promising and suitable 3D mesoporous support to overcome the diffusion of reactants into the porous network of heterogeneous catalysts.